2001
DOI: 10.1017/s0033291701003312
|View full text |Cite
|
Sign up to set email alerts
|

A cognitive model of the positive symptoms of psychosis

Abstract: In the last 10 years a consensus has developed that the symptoms of psychosis may be better understood by linking the steps between the phenomenological experiences and social, psychological and neurobiological levels of explanation. Cognitive models of psychosis are an important link in this chain. They provide a psychological description of the phenomena from which hypotheses concerning causal processes can be derived and tested; social, individual, and neurobiological factors can then be integrated via thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

113
1,080
4
29

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 1,296 publications
(1,226 citation statements)
references
References 48 publications
(43 reference statements)
113
1,080
4
29
Order By: Relevance
“…It is clear that anxiety is implicated across both cognitive and affective dimensions of paranoia, which is consistent with predictions of several cognitive models (Garety et al 2001;Morrison, 2001;Freeman et al 2002;Morrison et al 2011). Depression would be expected to be associated with paranoid conviction on the basis of several theories (Bentall et al 2001;Garety et al 2001;Morrison, 2001;Freeman et al 2002), while depressed mood would be expected to be associated with deservedness according to other predictions (Trower & Chadwick, 1995;Melo et al 2009); we found clear support for the former hypothesis and not the latter.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It is clear that anxiety is implicated across both cognitive and affective dimensions of paranoia, which is consistent with predictions of several cognitive models (Garety et al 2001;Morrison, 2001;Freeman et al 2002;Morrison et al 2011). Depression would be expected to be associated with paranoid conviction on the basis of several theories (Bentall et al 2001;Garety et al 2001;Morrison, 2001;Freeman et al 2002), while depressed mood would be expected to be associated with deservedness according to other predictions (Trower & Chadwick, 1995;Melo et al 2009); we found clear support for the former hypothesis and not the latter.…”
Section: Discussionsupporting
confidence: 87%
“…However, the relationship between negative beliefs about self and our dimensions of paranoia was the opposite, showing a differential relationship with deservedness and not paranoid ideation. This finding is consistent with specific predictions about deservedness (Trower & Chadwick, 1995;Melo et al 2009) but the lack of association with paranoid conviction is inconsistent with some models of paranoia (Bentall et al 2001;Garety et al 2001;Morrison, 2001;Freeman et al 2002) and with previous findings from patients with long-standing psychosis Bentall et al 2009), although previous studies have not generally considered paranoia and deservedness separately. The most likely explanation for the discrepancies between the findings is that the relationship between paranoia, feelings of deservedness and selfesteem are dynamic and vary during the progression of a psychotic illness.…”
Section: Discussionsupporting
confidence: 73%
“…In linewith this, themagnitude of the effect of online interventions for depressionwasmoderate for a group of neurological patients in two recent studies of whom most had never received specific treatment for depression before (Fischer et al, 2015;Schröder et al, 2014). Based on the assumption that depressive symptoms and depression-related cognitions (e.g., worry thinking style, negative beliefs about the self, interpersonal sensitivity, sleep disturbance) play a causal role for the emergence of positive symptoms (Garety et al, 2001;Freeman and Garety, 2014;Lincoln et al, 2014),we also expected the treatment to impact on positive symptoms.…”
Section: The Present Studymentioning
confidence: 90%
“…Cognitive models state that a key factor in the transition to psychotic symptoms is the negative interpretation or 'appraisal' of anomalous perceptual experiences [1][2][3][4][5]. Maladaptive appraisals endorsed by patients typically represent perceptions of externalised, personalised threat [6][7][8].…”
Section: Introductionmentioning
confidence: 99%